The potential of international coastal mass tourism destinations to generate creative capital - Romero-Padilla, Yolanda; Navarro-Jurado, Enrique; Malvárez-García, Gonzalo (Journal of Sustainable Tourism (Taylor&Francis), 2016)
This paper introduces a new line of research in international coastal mass tourism destinations. Such destinations have started to function in a more complex and potentially beneficial way, acting as transitional areas between the global city and local territory while at the same time developing their own unique characteristics. From this perspective, such destinations can potentially become environments for creativity and innovation, two factors that act as economic driving forces in the so-called “knowledge society”, thereby promoting the sustainable development of the destination from a socioeconomic perspective. The methodology used herein develops 10 indicators that are calculated and mapped out for two case studies which examine the same geographical context and comparable populations in order to demonstrate the creative capacity of a location whose economy is heavily reliant on tourism. The results show that tourist destinations have greater potential for generating creative capital than non-tourist destinations. Therefore, the consolidation of international mass tourism destinations as creative and innovative spaces which are capable of generating creative capital without losing their competitiveness as tourist destinations merits a reconception of their current role in global-local networks.
Keywords: Turismo - Evaluación; Creative class; Coastal tourism; Urbanisation process; Sustainable tourism; Tourist destinations